Comparison of panoramic radiography findings with CBCT findings in evaluation of the relation of impacted mandibular third molar tooth and inferior alveolar canal - B. Purtaji (The Journal of Qazvin University of Medical Sciences, 2017)
Background: In making a decision for extracting an impacted mandibular third molar tooth, assessing the risk of injury to inferior alveolar nerve is important. Objective: The aim of this study was to evaluate the correlation between the findings of panoramic radiography and CBCT in assessing the relationship between impacted mandibular third molar and inferior alveolar canal. Methods: In this descriptive-analytic study, electronic files of panoramic radiography of 132 patients referred to radiology department of Tehran school of dentistry were studied (2012-14). Ninety-two files were selected only from types by darkening of the apex of impacted mandibular third molar or interference with the white line of the mandibular canal in panoramic view. Their contact with mandibular canal were also investigated in cross sectional CBCT views. Findings: In males and females there was a high relation between panoramic and CBCT diagnosis in cases of darkening of the root and interference with the white line (P<0.001). Sensitivity and specificity for the detection of interference with white line in right side was 95.5% and 85.7% and for the left side was 83.3% and 90%. The sensitivity and specificity for darkening of the third molar apex in right side were 95.5% and 92.5% and in left side were 82.5% and 91.3%. Conclusion: There is too much relation between panoramic diagnosis in cases of darkening of the roots and interference of roots with the white border of mandibular canal and CBCT diagnosis from this point of view that there is a close contact with mandibular canal.